Parameter estimation and outlier detection for some types of circular model - Siti Zanariah, Satari (2015)
This study focuses on the parameter estimation and outlier detection for some types of the circular model. We first look at the concentration parameter of von Mises distribution. The von Mises distribution is the most commonly used probability distribution of a circular random variable, and the concentration of a circular data set is measured using the mean resultant length. We propose a new and efficient approximation of the concentration parameter estimates using two approaches, namely, the roots of a polynomial function and minimizing the negative value of the log-likelihood function in this study.